Economic transformation and growth in the Philippines: An analysis of political settlements, rents, and deals - Jesus Felipe; Edgar Desher; Brendan Miranda (Levy Economics Institute of Bard College, 2023)
The main gateway for the Philippines to develop and become an upper-middle-income economy - and eventually, a high-income economy - is to expedite the shift of workers out of agriculture and to produce and export more complex products with a higher income elasticity of demand. The actual growth rate is constrained by the balance-of-payments equilibrium growth rate, about 6 percent-the maximum the country can attain without incurring balance-ofpayments problems. We use the Pritchett-Sen-Werker political-economy framework to analyze the roles of different types of firms and the deals environment from successive Philippine administrations until the current one. Due to their economic size and political power, only the nation's conglomerates will be able to lead the transformation of the economy. However, the country's large groups do not have incentives nor do they see the need to shift to the production and export of tradables. Without this transformation, the country will be able to register positive growth but will not become an internationally competitive economy, and will not be able to achieve, and especially maintain, the growth rate targeted by the current administration: 6.5-8 percent per annum during 2023-28.
Keywords: O11; O40; O43; O53; 330; economic transformation; deals; Philippines; political settlements; rents